Biomedicine Innovations and Its Nanohydrogel Classifications - Sifiso S. Makhathini; Sipho Mdanda; Pariksha J. Kondiah; Moosa E. Kharodia; Karl Rumbold; Imhotep Alagidede; Yashwant Pathak; Zain Bulbulia; Thankhoe A. Rants'o; Pierre P. D. Kondiah (MDPI AG, 2022)
As one of the most cutting-edge and promising polymer crosslinked network nanoparticle systems. Polymer nano-sized hydrogels (nanogels) have been a hot topic in the biomedical field over the last few decades. Due to their unique characteristics, which include their relatively high drug encapsulation efficiency, ease of preparation, high tunability, low toxicity, high stability in serum and responsive behavior to a range of stimuli to facilitate drug release. Nanogels are thought to be the next generation of drug delivery systems that can completely change the way that drug delivery systems have an impact on patients' lives. Nanogels have demonstrated significant potential in a variety of fields, including chemotherapy, diagnosis, organ targeting, and delivery of bioactive molecules of different dimensions. However, the lack of substantial clinical data from nanogels becomes one of the major barriers to translating the nanogel concept into a practical therapeutic application for many disease conditions. In addition, nanogel safety profiles have been the major concern that hinders it advancement to the clinical trial phase. This review aims to emphasize the unique properties of nanogels as delivery systems for a variety of bioactive molecules over other nano-delivery systems. Also, this review attempts to give insight into the recent progress in nanogels as a carrier in the field of nanomedicine to overcome complex biological barriers. Relevant scientific data and clinical rationale for the development and the potential use of nanogel as a carrier for targeted therapeutic interventions are discussed. Finally, the concluding points of this review highlight the importance of understanding the long-term toxicity profile of nanogel within the biological system to fully understand their biocompatibility.